De Novo Splice Site Variant of TCF12 in a Boy With Isolated Kallmann Syndrome - Erina Suzuki; Hirohito Shima; Aki Ueda; Kazuhiko Nakabayashi; Keiko Matsubara; Yoko Kuroki; Junko Kanno; Maki Fukami (Case Reports in Endocrinology, 2025)
Conclusion: These results broaden the mutation spectrum of TCF12. More importantly, this study argues for the etiological relationship between TCF12 variants and isolated Kallmann syndrome.